2013
DOI: 10.1371/journal.pone.0069251
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Multiarmed Spiral Waves in a Regular Network of Neurons

Abstract: Formation and selection of multiarmed spiral wave due to spontaneous symmetry breaking are investigated in a regular network of Hodgkin-Huxley neuron by changing the excitability and imposing spatial forcing currents on the neurons in the network. The arm number of the multiarmed spiral wave is dependent on the distribution of spatial forcing currents and excitability diversity in the network, and the selection criterion for supporting multiarmed spiral waves is discussed. A broken spiral segment is measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 67 publications
3
25
0
Order By: Relevance
“…In this way, some researchers show great interests in detecting the formation and transition of patterns in network of neurons [9][19]. It was reported that spiral wave can be found in the cortex of brain [20][22], and then some theoretical investigations [23], [24] have been presented to explore the potential formation mechanism of spiral wave and multi-armed spiral wave in the network of neurons, indeed, these results [24] have confirmed that intermediate channels blocking in neurons in a local area of neuronal network can induce emergence of spiral wave, and the stability of multiarmed spiral wave was also discussed. It was also confirmed that artificial defects [25] can block travelling wave to induce perfect spiral wave under appropriate coupling intensity between neurons, and breakup of spiral wave occurs with strong noise or channel noise [26], [27] being used.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, some researchers show great interests in detecting the formation and transition of patterns in network of neurons [9][19]. It was reported that spiral wave can be found in the cortex of brain [20][22], and then some theoretical investigations [23], [24] have been presented to explore the potential formation mechanism of spiral wave and multi-armed spiral wave in the network of neurons, indeed, these results [24] have confirmed that intermediate channels blocking in neurons in a local area of neuronal network can induce emergence of spiral wave, and the stability of multiarmed spiral wave was also discussed. It was also confirmed that artificial defects [25] can block travelling wave to induce perfect spiral wave under appropriate coupling intensity between neurons, and breakup of spiral wave occurs with strong noise or channel noise [26], [27] being used.…”
Section: Introductionmentioning
confidence: 99%
“…In a word, the way to induce local heterogeneity is different from the case as shown in Ref. 43, thus another mechanism to explain the emergence of multi-armed spiral waves in excitable media can be discussed in a numerical way.…”
Section: Introductionmentioning
confidence: 93%
“…As a result, it is important to investigate the stability of multi-armed spiral wave in the excitable media. Hu et al 43 attempted to reproduce the occurrence of multi-armed spiral waves in a network of neurons and the stability of multi-armed spiral waves was also discussed analytically. They found that a group of target waves can be emitted from local heterogeneity by imposing external forcing currents with diversity on the network, and then these target waves can convert into spiral waves due to continuous collision.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical properties of electric activities, stochastic resonance, coherence and synchronization of neurons have been investigated extensively [3][4][5][6][7][8][9][10][11][12][13][14]. Furthermore, the collective behaviors of neuronal network have also been investigated by detecting the spatiotemporal pattern selection, transition of spatial distribution , such as pulse wave [20] in a ring network, target wave [30], spiral wave [16][17][18][19][31][32][33][34] in a two-dimensional array with different topological structures. In fact, in realistic neuronal system, the effect of other factors should be considered, for example, the action potential is also dependent on the gliocyte and it is interesting to study the cooperative behaviors of neuron and astrocyte [35].…”
Section: Introductionmentioning
confidence: 99%